Phase Congruency for damage mapping with guided wavefields. (December 2017) - Darnton, A.; Ruzzene, M.
Abstract: The Phase Congruency for damage mapping method utilizes full guided wavefield measurements to visualize the extent of subsurface damage in plate-like structures. The method exploits the phase of wavefield components calculated from a filter bank decomposition of the wavefield in space. Testing for alignment of phase between components over the measurement domain generates a plot of discontinuities in the wavefield. Discontinuities in the wavefield indicate the existence and extent of damage in the specimen considered. Damage maps for a host of cases ranging from simple changes in thickness to complex impact damage are presented. Highlights: Technique for mapping damage in plates is presented. Guided wave interrogation via a single piezoelectric element illuminates damage. Phase in the spatial domain is used to map damage. Method is demonstrated on a range of damage specimen.